Konflik Pembangunan Jalan Padang ByPass, 2015-2018 - Pramida, Cici; Husodo, Purwo (Laboratorium Sejarah, Departement Ilmu Sejarah, Fakultas Ilmu Budaya, Universitas Andalas, 2023)
This research focuses on the chronology of conflict between the people of Padang City, which resulted from the development of the Padang ByPass Road with the City Government. These two groups are at odds, causing conflicts and blockades along the Padang ByPass Road. The research method used is the historical method consisting of four stages, starting from searching and collecting sources (heuristics). In collecting sources, sources that discuss the conflict of the Padang ByPass Road were gathered both in writing and orally. Criticizing and selecting the data obtained into facts (critique). Interpreting and selecting that makes sense (interpretation). The stage of writing research results (historiography). The construction of the first Padang ByPass Road in 1990, followed by the second stage in 2015 in Padang City, caused conflict because the Padang City Government did not provide adequate compensation according to the previous agreement with the affected community. The land was not individual land, but customary land owned by the community. This made the community angry and blockaded several points along the Padang ByPass Road. Some of the ways the government took to resolve the conflict include the negotiation process between the community and the government. However, if the negotiation process does not go smoothly or as expected, it will be followed by a legal process.